N-heterocyclic-carbene-catalyzed regioselective oxidative ring-opening of epoxides with aromatic aldehydes: a facile entry to alpha-acyloxyketones - Reddi, Rambabu N.; Gontala, Arjun; Prasad, Pragati K.; Sudalai, Arumugam (Asian Journal of Organic Chemistry, 2016)
A high-yielding synthesis of -acyloxyketones using a N-heterocyclic-carbene (NHC)-catalyzed, oxidative ring-opening of epoxides with aromatic aldehydes is described. This regioselective, oxidative process utilizes a N-bromosuccinimide (NBS)/DMSO combination as the oxidant system and Et3N as the base under mild reaction conditions.
Keywords: aldehydes; epoxides; halogen oxidants; N-heterocyclic carbenes; oxygen